Kualitas Pelayanan Terpadu Pada Penyelenggaraan Mal Pelayanan Publik Kota Sidoarjo - Saptaningtyas Dwi Pertiwi; Indah Murti (Jurnal Kemitraan Masyarakat, 2024)
In general, everyone needs service, in fact, it can usually be said that service cannot be separated from human life. According to Moenir (2002: 6). A service is an activity provided by an intangible group or individual that cannot be owned by a consumer, that is, someone who benefits from the activities of the organization providing the service. According to Dwiyanto (2005: 141) said: "Public services can be interpreted as several activities that aim to meet the needs of the community and are provided by the public bureaucracy. In public services, the state has an obligation to always make a development in the services provided in order to realize quality public services, by carrying out quality public services can create good governance. In connection with the establishment of Sidoarjo Regency as one of the Public Service Mall Organizing Districts based on the Decree of the Minister of State Apparatus Empowerment and Bureaucratic Reform Number 11 of 2018 concerning the Determination of the Location for the Implementation of Public Service Malls in 2018, as well as in the framework of orderly administration of the Implementation of Public Service Malls. This study aims to find out how effective services are at the Sidoarjo City Public Service Mall.